Pengaruh Kompensasi, Motivasi, dan Komitmen Organisasional terhadap Kinerja Karyawan di PT IDS Medical System Indonesia Cabang Medan - Alfian Alfian; Junita Astramia (JURNAL PUNDI, 2020)
Improving employee performance giving compensation and motivation is an indicator that can affect employee performance. However, every company has an organization. Organizations have commitments called organizational commitment. With all these variables can improve employee performance at PT. IDS Medical System Indonesia Medan Branch. In the study, it shows that the variable X1 is Compensation, Variable X2 is Motivation and Variable X3 Organizational Commitment called the free variable. While for the dependent variable is the performance of employee Y. for the population and sample in this study amounted to 80 people. The results of the study that the variable compensation and motivation have a significant effect on the performance of employees with a sig value <0.05. However, for organizational commitment variables not so influential with employee performance with a sig value> 0.05.Keywords: Compensation, Motivation, Organizational Commitment, Employee Performance.